Chemical compounds investigation and profiling of antimicrobial and antiviral constituents of Tephrosia purpurea subsp. apollinea - Ahmed M. M. Youssef; Doaa A. M.‎ Maaty; Yasser Gaber (Journal of Biological Research, 2024)
Tephrosia purpurea subsp. apollinea belongs to the family Fabaceae, and it is distributed in the delta region of Egypt. It has been used in traditional medicine for the management of various diseases. This study aimed to identify the phytochemicals utilizing LC/MS, and biological properties of a methanolic extract of Tephrosia purpurea subsp. apollinea. The analysis identified 31 compounds representing various phytochemical classes, including fatty acids, sterols, phenolic acids, polyphenols, terpenoids, and flavonoids. Among the major compounds detected, linoleic acid (13.2%) and campesterol (10.1%) were the most abundant. The extract displayed antibacterial, antifungal, and antiviral activities. The methanolic extract demonstrated varying degrees of antimicrobial activity against the tested microorganisms, with Bacillus subtilis showing the highest susceptibility. Significant antiviral activity was observed against herpes simplex and hepatitis C viruses. These findings highlight the potential of T. purpurea subsp. apollinea as a valuable source of natural bioactive compounds including antiviral agents. Additional investigation is required to explore the active principles responsible for the observed biological properties and their therapeutic applications in combating bacterial, fungal, and viral infections.